High-stability lithium iron phosphate battery positive plate and preparation method thereof
Patent Information
- Application Number
- CN202611006416.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-07
- Publication Date
- 2026-10-23
AI Technical Summary
然而,现有高压实磷酸铁锂正极片存在以下不足:1)孔隙率极低导致浸润性差,电解液难以深层渗透,注液效率低下且易形成局部干涸,严重增加内阻并诱发析锂;2)层间结合强度不足,虽然材料本身极其稳定,但在数千乃至上万次充放电的交变应力下,极片依然容易发生层间脱落或活性物质粉化
[0020]与现有技术相比,本发明至少具有以下有益效果:本发明打破了传统粘结剂依靠纯物理范德华力的局限,构建了物理咬合和化学键合的超强联结网络。首先,对铝箔电晕激发-OH;其次,通过化学处理赋予稳定的LFP颗粒表面-OH;最后,采用聚丙烯酸和羧甲基纤维素交联。在烘烤热场中,聚丙烯酸不仅与羧甲基纤维素交联形成坚韧的高分子骨架,其大量过剩的游离-COOH还会同时与铝箔表面的-OH、以及LFP表面的-OH发生酯化反应。这相当于通过化学共价键在集流体-粘结剂网络-活性颗粒之间打下了分子级铆钉,使得极片具备了极高的抗剥离能力。在此基础上结合表面可溶性功能涂层,即使涂层溶解形成微通道,这种刚柔并济的化学锚固网络也能牢牢锁住颗粒与集流体,极片也不会因此松散或脱层,确保了长循环下的高结构稳定性。
Smart Images

Figure CN122968246A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium iron phosphate battery cathode preparation technology, and particularly relates to a highly stable lithium iron phosphate battery cathode sheet and its preparation method. Background Technology
[0002] With the explosive growth of new energy vehicles and large-scale energy storage systems, the market has placed stringent demands on the cycle life, safety, and cost of lithium-ion batteries. The main lithium batteries on the market include lithium iron phosphate (LFP), ternary lithium batteries (NCM / NCA), and lithium cobalt oxide (LCO), but in the power and energy storage market, lithium iron phosphate and ternary lithium batteries account for the vast majority of the market share. Compared to ternary materials, lithium iron phosphate (LiFePO4) materials have a unique olivine structure and PO4 content. 3- The strong polar covalent bonds in lithium iron phosphate (PO) give it excellent chemical and thermal stability, and its structure is not easily damaged during charge and discharge, thus exhibiting long cycle life. However, the energy density of lithium iron phosphate batteries is lower than that of ternary lithium batteries.
[0003] In pursuit of higher energy density, high-density lithium iron phosphate (LFP) battery manufacturing commonly employs high-density processes. However, existing high-density LFP cathode sheets have the following shortcomings: 1) Extremely low porosity leads to poor wettability, making it difficult for electrolyte to penetrate deeply, resulting in low injection efficiency and easy formation of localized drying, which severely increases internal resistance and induces lithium plating; 2) Insufficient interlayer bonding strength. Although the material itself is extremely stable, under alternating stress of thousands or even tens of thousands of charge-discharge cycles, the electrode sheet is still prone to interlayer delamination or active material pulverization.
[0004] In existing technologies, to solve the wetting problem, a design is used to coat the electrode surface with a coating soluble in electrolyte to construct microchannels. However, this simple liquid-conducting channel construction only focuses on fluid dynamics and ignores the fact that the dissolution of the channel will cause local compaction and loosening of the structure, thereby significantly weakening the already insufficient interlayer bonding of the electrode.
[0005] Therefore, there is an urgent need for a highly stable lithium iron phosphate cathode sheet and its preparation method that can establish an efficient wetting network in all directions and greatly enhance the interlayer bonding strength at the microscopic level. Summary of the Invention
[0006] The purpose of this invention is to address the shortcomings of existing technologies by providing a highly stable lithium iron phosphate battery cathode and its preparation method, enabling the lithium iron phosphate cathode to simultaneously possess excellent deep wetting rate and ultra-high anti-delamination stability under long-cycle conditions.
[0007] To achieve the above objectives, the present invention provides the following technical solution: A highly stable lithium iron phosphate battery cathode, comprising: The modified aluminum foil treated with corona discharge has a micro-rough structure on its surface and is grafted with hydroxyl functional groups. A positive electrode active material layer is coated on at least one surface of the modified aluminum foil, the positive electrode active material layer comprising lithium iron phosphate positive electrode active material, a conductive agent and a crosslinking composite binder; the surface of the lithium iron phosphate positive electrode active material is hydroxylated and grafted with surface hydroxyl groups; A soluble functional coating is formed by intermittently coating the surface of the positive electrode active material layer and curing it. The soluble functional coating extends through the width direction of the positive electrode sheet and is used to dissolve and form a flow channel when the electrolyte is injected. The crosslinked composite adhesive is a composite adhesive with a three-dimensional network structure formed by in-situ crosslinking of polyacrylic acid (PAA) and carboxymethyl cellulose (CMC) through an esterification condensation reaction. The crosslinked composite adhesive contains free carboxyl groups that have not participated in the esterification condensation reaction. The free carboxyl groups undergo in-situ dehydration condensation reactions with the hydroxyl functional groups on the surface of the modified aluminum foil and the hydroxyl groups on the surface of the lithium iron phosphate positive electrode active material, respectively, to form a three-dimensional covalent bonded network of "current collector-adhesive-active material".
[0008] Preferably, the characteristic parameters of the soluble functional coating satisfy the following relationship:
[0009]
[0010] Where: W is the width of a single functional coating, in μm; H is the thickness of a single functional coating, in μm; T is the thickness of the positive electrode active material layer after roll forming, in μm; D is the spacing between two adjacent functional coatings, in μm; d 50 The median particle size of the lithium iron phosphate cathode active material is expressed in μm.
[0011] Preferably, the soluble functional coating comprises the following components in weight percentages: 40% to 60% of the rapid solvent is selected from at least one of fluoroethylene carbonate (FEC) and ethylene carbonate (EC); 30% to 50% of the polymer gel backbone is selected from at least one of polyethylene oxide (PEO) and polyvinylpyrrolidone (PVP); 5% to 15% of inorganic nanopropellers, selected from at least one of nano-silica and nano-alumina, with a particle size of 15 to 50 nm.
[0012] Preferably, in the positive electrode active material layer, the mass ratio of polyacrylic acid (PAA) to carboxymethyl cellulose (CMC) is (4~6):(1~1.5); to ensure that the polyacrylic acid has an excess of free carboxyl groups after esterification reaction with the carboxymethyl cellulose.
[0013] Preferably, the conductive agent is a composite conductive agent of one-dimensional carbon nanotubes and zero-dimensional conductive carbon black (Super P), with a mass ratio of (1~3):(2~4).
[0014] Preferably, along the width direction of the positive electrode sheet, the thickness H of the soluble functional coating exhibits a distribution characteristic of gradually decreasing from the central region of the positive electrode sheet to the two side edge regions.
[0015] Preferably, the water contact angle of the modified aluminum foil surface is controlled between 10° and 30°, and the surface roughness Ra is 0.3 to 0.8 μm.
[0016] Preferably, in a unit mass of the lithium iron phosphate cathode active material, the molar content of hydroxyl groups grafted on its surface is 20~60 μmol / g, and the complete olivine crystal structure is retained.
[0017] Preferably, the soluble functional coating on the surface of the positive electrode active material layer appears as parallel straight stripes, obliquely intersecting grids, or discontinuous dotted and dashed arrays.
[0018] Furthermore, the present invention also provides a method for preparing the high-stability lithium iron phosphate battery cathode sheet as described above, comprising the following steps: S1. Place the original lithium iron phosphate powder in a mixed aqueous solution containing hydrogen peroxide and dilute ammonia, and perform gentle hydrothermal stirring at 50℃~70℃ for 1~3h. After filtration, washing and drying, hydroxylated lithium iron phosphate positive electrode active material with hydroxyl groups grafted on the surface is obtained. S2. The positive electrode current collector aluminum foil is subjected to corona discharge treatment to obtain a modified aluminum foil with a micro-rough surface structure and grafted hydroxyl functional groups. S3. The hydroxylated lithium iron phosphate positive electrode active material, conductive agent, polyacrylic acid and carboxymethyl cellulose are mixed evenly to form an aqueous positive electrode slurry, which is uniformly coated on at least one surface of the modified aluminum foil. After staged drying and rolling, a substrate positive electrode sheet is obtained. In the high temperature vacuum stage of staged drying, polyacrylic acid and carboxymethyl cellulose undergo esterification condensation reaction to form a crosslinked composite binder, and the free carboxyl groups undergo in-situ condensation reaction with the hydroxyl groups on the surface of the modified aluminum foil and the hydroxyl groups on the surface of the hydroxylated lithium iron phosphate positive electrode active material. S4. On the surface of the positive active material layer of the substrate positive electrode sheet, the soluble functional coating is coated at intervals and vacuum cured at room temperature to form the lithium iron phosphate battery positive electrode sheet.
[0019] Preferably, in step S3, the staged drying sequentially includes: an atmospheric pressure initial drying and dehydration stage at a temperature of 75℃~95℃ and a time of 0.5~1.5h; and a vacuum high-temperature crosslinking stage at a vacuum degree ≤-0.095MPa, a temperature of 140℃~160℃, and a holding time of 3~6h.
[0020] Compared with existing technologies, this invention has at least the following beneficial effects: This invention breaks through the limitations of traditional adhesives relying solely on purely physical van der Waals forces, constructing a super-strong bonding network of physical interlocking and chemical bonding. First, corona discharge of aluminum foil induces -OH groups; second, chemical treatment imparts stable -OH groups to the surface of LFP particles; finally, crosslinking with polyacrylic acid and carboxymethyl cellulose is employed. In the baking thermal field, polyacrylic acid not only crosslinks with carboxymethyl cellulose to form a tough polymer backbone, but its abundant excess free -COOH groups also undergo esterification reactions with the -OH groups on the aluminum foil surface and the LFP surface. This is equivalent to establishing molecular-level rivets between the current collector, adhesive network, and active particles through chemical covalent bonds, giving the electrode extremely high anti-peeling ability. Based on this, combined with a surface-soluble functional coating, even if the coating dissolves to form microchannels, this rigid-flexible chemical anchoring network can firmly lock the particles and current collector, preventing the electrode from loosening or delaminating, ensuring high structural stability under long-term cycling. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the positive electrode sheet in one embodiment of the present invention.
[0022] In the figure: 1. Modified aluminum foil; 2. Positive electrode active material layer; 3. Soluble functional coating. Detailed Implementation
[0023] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0025] In accordance with the first aspect of this application, such as Figure 1 As shown, this application provides a highly stable lithium iron phosphate battery cathode sheet, comprising: The modified aluminum foil 1, which has undergone corona discharge treatment, has a micro-rough structure on its surface and is grafted with hydroxyl functional groups. A positive electrode active material layer 2 is coated on at least one surface of the modified aluminum foil 1. The positive electrode active material layer 2 includes lithium iron phosphate positive electrode active material, conductive agent and cross-linking composite binder; the surface of the lithium iron phosphate positive electrode active material is hydroxylated and grafted with surface hydroxyl groups. A soluble functional coating 3 is formed by intermittently coating the surface of the positive electrode active material layer 2 and curing it. The soluble functional coating 3 extends through the width direction of the positive electrode sheet and is used to dissolve and form a flow channel when the electrolyte is injected. The crosslinking composite adhesive is a composite adhesive with a three-dimensional network structure formed by in-situ crosslinking of polyacrylic acid (PAA) and carboxymethyl cellulose (CMC) through an esterification condensation reaction. The crosslinking composite adhesive contains free carboxyl groups that have not participated in the esterification condensation reaction. The free carboxyl groups undergo in-situ dehydration condensation reactions with the hydroxyl functional groups on the surface of the modified aluminum foil and the hydroxyl groups on the surface of the lithium iron phosphate cathode active material, respectively, to form a three-dimensional covalent bonded network of "current collector-adhesive-active material".
[0026] This invention breaks through the limitations of traditional physical van der Waals forces in bonding, constructing a super-strong network of physical interlocking and chemical bonding. First, aluminum foil is corona-treated to roughen it and generate -OH groups; second, LFP particles are endowed with -OH groups; finally, polyacrylic acid (PAA) and carboxymethyl cellulose (CMC), rich in -COOH groups, are cross-linked. Under the baking thermal field, PAA and CMC cross-link to form a tough framework, while the excess -COOH groups in PAA undergo esterification reactions downwards with the -OH groups on the aluminum foil and upwards with the -OH groups on the LFP surface. This "covalent bridge" from the current collector directly to the surface of the active particles gives the electrode extremely high anti-peeling ability. Based on this, combined with a surface-soluble functional coating, even if the coating dissolves to form microchannels, this flexible yet rigid chemical anchoring network can firmly lock the particles and the current collector, ensuring high structural stability under long-term cycling.
[0027] In one embodiment according to this application, the characteristic parameters of the soluble functional coating 3 satisfy the following relationship:
[0028]
[0029] Where: W is the width of a single functional coating, in μm; H is the thickness of a single functional coating, in μm; T is the thickness of the positive electrode active material layer 2 after roll forming, in μm; D is the spacing between two adjacent functional coatings, in μm; d50 is the median particle size of the lithium iron phosphate positive electrode active material, in μm.
[0030] In this invention, the relationship between functional coating parameters is limited to... This relationship precisely couples the macroscopic dimensions of the coating with the microscopic resistance parameters of the electrode: the numerator W·H represents the cross-sectional area of the coating, i.e., the liquid storage capacity of the channel provided after dissolution; the denominator combines the coating distribution density (D) and the characteristic length of the substrate capillary resistance (D). If the calculated value is below 1.5, the liquid storage channel is too narrow and insufficient to overcome the fluid wetting resistance of the high-pressure solid electrode, resulting in insignificant improvement in wetting. If it is above 5.5, the coating duty cycle is too large, resulting in excessive loss of solid-solid support contact area, which leads to the collapse of the internal skeleton of the electrode caused by the dissolution of the channel later. Limiting this range can achieve the best balance between high wetting and high mechanical support.
[0031] In one embodiment according to this application, the soluble functional coating 3 comprises the following components by mass percentage: 40% to 60% of the rapid solvent is selected from at least one of fluoroethylene carbonate (FEC) and ethylene carbonate (EC); 30% to 50% of the polymer gel backbone is selected from at least one of polyethylene oxide (PEO) and polyvinylpyrrolidone (PVP); 5% to 15% of inorganic nanopropellers, selected from at least one of nano-silica and nano-alumina, with a particle size of 15 to 50 nm.
[0032] Among them, FEC / EC is used as a fast dissolving agent, which dissolves extremely quickly and FEC is a beneficial film-forming additive; PEO / PVP swells after absorbing liquid to form a gel network, which does not hinder lithium-ion transport; inorganic nano silica / alumina acts as a rigid support agent, which always plays the role of "microscopic pier" in the long-term volume stress change, keeping the liquid guiding gap from being squeezed and closed, and realizing the flow guiding throughout the entire life cycle.
[0033] In one embodiment of this application, the mass ratio of polyacrylic acid (PAA) to carboxymethyl cellulose (CMC) in the positive electrode active material layer 2 is (4~6):(1~1.5); to ensure that the polyacrylic acid has an excess of free carboxyl groups after esterification reaction with carboxymethyl cellulose.
[0034] The specified mass ratio of (4~6):(1~1.5) ensures that a large number of unreacted excess free carboxyl groups are retained after the PAA and CMC crosslinking reaction. This is a key prerequisite for achieving multi-terminal in-situ esterification condensation reaction.
[0035] In one embodiment of this application, the conductive agent is a composite conductive agent of one-dimensional carbon nanotubes and zero-dimensional conductive carbon black (Super P), with a mass ratio of (1~3):(2~4). One-dimensional carbon nanotubes and zero-dimensional Super P are introduced. The carbon nanotubes have a high aspect ratio and can be intercalated within the cross-linked polymer network of PAA-CMC, acting like "steel bars" in reinforced concrete. This not only improves the overall conductivity of the electrode but also further enhances its resistance to tensile stress from the minute volume expansion of LFP, preventing the conductive network from breaking.
[0036] In one embodiment according to this application, the thickness H of the soluble functional coating 3 along the width direction of the positive electrode sheet exhibits a gradient decreasing characteristic from the central region to the two side edges. Specifically, the coating thickness H decreases from the center to the sides because, in large-scale energy storage or power battery electrolyte filling, the electrolyte typically flows in from the edges; the central region is the most difficult to wet and has the worst heat dissipation; a thicker coating at the center allows for the formation of a larger electrolyte reservoir after dissolution, thereby balancing the electrolyte distribution across the entire electrode surface and eliminating dry-core phenomena.
[0037] In one embodiment according to this application, the water contact angle of the modified aluminum foil 1 surface is controlled between 10° and 30°, and the surface roughness Ra is 0.3 to 0.8 μm. Preferably, the corona discharge treatment conditions are: under an oxygen-containing atmosphere, the corona power is 1.5 to 3.0 kW, and the treatment time is 10 to 20 s.
[0038] In one embodiment of this application, the molar content of hydroxyl groups grafted onto the surface of the lithium iron phosphate (LFP) cathode active material per unit mass is 20-60 μmol / g, while retaining a complete olivine crystal structure. Specifically, this invention uses the molar content of grafted hydroxyl groups (20-60 μmol / g) for precise characterization. This indicator can be accurately determined using standard methods such as chemical titration or thermogravimetric analysis, ensuring sufficient density of hydroxyl groups for condensation bonding while avoiding excessive corrosion that could damage the olivine lattice structure of the LFP powder.
[0039] In one embodiment of this application, the soluble functional coating 3 on the surface of the positive electrode active material layer 2 appears as parallel straight stripes, obliquely intersecting grids, or discontinuous dotted and dashed arrays.
[0040] According to a second aspect of this application, this application also provides a method for preparing the above-mentioned highly stable lithium iron phosphate battery cathode sheet, comprising the following steps: S1. Place the original lithium iron phosphate powder in a mixed aqueous solution containing hydrogen peroxide and dilute ammonia, and perform gentle hydrothermal stirring at 50℃~70℃ for 1~3h. After filtration, washing and drying, hydroxylated lithium iron phosphate positive electrode active material with hydroxyl groups grafted on the surface is obtained. S2. The positive electrode current collector aluminum foil is subjected to corona discharge treatment to obtain modified aluminum foil 1 with a micro-rough surface structure and grafted hydroxyl functional groups. S3. Hydroxylated lithium iron phosphate positive electrode active material, conductive agent, polyacrylic acid and carboxymethyl cellulose are mixed evenly to form an aqueous positive electrode slurry, which is uniformly coated on at least one surface of modified aluminum foil 1. After staged drying and rolling, a substrate positive electrode sheet coated with positive electrode active material layer 2 is obtained. In the high temperature vacuum stage of staged drying, polyacrylic acid and carboxymethyl cellulose undergo esterification condensation reaction to form a cross-linked composite binder, and free carboxyl groups undergo in-situ condensation reaction with hydroxyl groups on the surface of modified aluminum foil 1 and hydroxyl groups on the surface of hydroxylated lithium iron phosphate positive electrode active material. S4. A soluble functional coating 3 is formed by intermittently coating and vacuum curing at room temperature on the surface of the positive active material layer 2 of the substrate positive electrode sheet, thus obtaining the lithium iron phosphate battery positive electrode sheet.
[0041] In one embodiment of this application, step S3, the staged drying sequentially includes: an atmospheric pressure initial drying and dehydration stage with a temperature of 75℃~95℃ and a time of 0.5~1.5h; and a vacuum high-temperature crosslinking stage with a vacuum degree ≤-0.095MPa, a temperature of 140℃~160℃, and a holding time of 3~6h.
[0042] In S1, a mild hydrothermal treatment method using hydrogen peroxide and dilute ammonia is employed. Hydrogen peroxide provides strong oxidizing properties to create oxygen defects on the surface, while ammonia provides an alkaline environment to promote hydrolysis and generate -OH. This mild environment ensures that the surface hydroxyl density meets the requirements for subsequent bonding without damaging the extremely core olivine-type crystal framework inside the LFP, thus guaranteeing the material's cycle life.
[0043] Among these processes, the staged baking in S3 is crucial; the initial baking at atmospheric pressure and gentle dehydration prevent the electrode from bubbling, while the subsequent high vacuum (≤-0.095MPa) and high temperature (140℃~160℃) are extremely critical. According to Le Chatelier's principle, the high vacuum continuously removes water molecules generated by the dehydration condensation reaction, strongly disrupting the chemical equilibrium and pushing the dehydration condensation reaction in the forward direction. This drives the -COOH in PAA to complete esterification and cross-linking with the -OH on the aluminum foil and LFP, which is the cornerstone for the solidification and formation of the chemical bonding network.
[0044] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.
[0045] Example 1
[0046] A method for preparing a highly stable lithium iron phosphate battery cathode: S1, LFP hydroxylation modification: Commercially available lithium iron phosphate (LFP, median particle size d) is modified by hydroxylation of LFP. 50=2μm) powder was added to a mixed solution containing 5% hydrogen peroxide and 0.5mol / L ammonia, and treated with magnetic stirring at 60℃ for 2h. After filtration, washing with pure water multiple times, and drying under vacuum at 80℃, the molar content of hydroxyl groups on the surface of the LFP was determined to be 45μmol / g by acid-base titration.
[0047] S2. Corona treatment of aluminum foil: A 15μm thick aluminum foil is subjected to continuous corona discharge treatment in an air atmosphere. The corona power is 2.0kW and the treatment time is 15s, resulting in a modified aluminum foil with a roughness Ra of 0.5μm and a surface grafted with -OH.
[0048] S3, Electrode coating and curing crosslinking: Preparation of cross-linked composite adhesive: PAA and CMC are mixed in deionized water at a mass ratio of 5:1 to form a carboxyl-rich aqueous adhesive solution.
[0049] Preparation of slurry: The above-mentioned hydroxylated LFP, conductive agent (CNT to Super P mass ratio 2:3), and above-mentioned composite binder are mixed at a solid content mass ratio of 95:3:2 to prepare positive electrode slurry.
[0050] Coating and Baking: The slurry is uniformly coated onto the modified aluminum foil. The first stage involves initial drying at 85℃ under normal pressure for 1 hour to remove moisture. The second stage involves holding the foil in a vacuum oven at -0.098MPa and 150℃ for 4 hours. Under this high temperature and high vacuum, PAA and CMC undergo intermolecular cross-linking, and the free -COOH of PAA undergoes deep esterification, dehydration, and condensation with the -OH and LFP-OH of the aluminum foil, forming a covalent bond of "current collector-bonding network-active particles". After roll forming, the electrode thickness T = 100μm.
[0051] S4. Preparation of soluble coating: The coating solution consists of EC (50%), PEO (40%), and nano-SiO2 (10%, particle size 20nm) dispersed in a low-boiling-point solvent. Parallel straight stripe patterns are applied alternately to the substrate electrode and cured under vacuum at room temperature.
[0052] Parameter design: Coating width W = 800 μm, thickness H = 4 μm, spacing D = 150 μm. Substitute into the formula for calculation: The value falls within the range of 1.5 to 5.5. A cylindrical battery cell A1 is thus obtained.
[0053] Example 2
[0054] The basic steps are the same as in Example 1, the only difference being the size and arrangement parameters of the soluble coating: The coating is designed with a width W = 1000 μm, a thickness H = 6 μm, and a spacing D = 120 μm. The electrode thickness T = 100 μm, d 50 =2μm.
[0055] Substitute into the formula to calculate: The value meets the range of 1.5~5.5. A cylindrical battery cell A2 is thus produced.
[0056] Example 3
[0057] The basic steps are the same as in Example 1, except that the soluble functional coating on the electrode surface exhibits a thickness gradient distribution. From the center line of the positive electrode width towards both sides, the thickness H of a single coating gradually and smoothly decreases from 6 μm to 2 μm, further improving the drought phenomenon in the center of the cell during large-core electrolyte injection. Cylindrical cell A3 is thus obtained.
[0058] Comparative Example 1
[0059] Reference electrode: Ordinary LFP powder without hydroxylation treatment and smooth aluminum foil without corona treatment. The binder is conventional non-crosslinked PVDF (NMP as solvent). No functional coating is applied to the positive electrode surface. The electrode is dried and rolled at 120℃ using standard processes to produce cell B1.
[0060] Comparative Example 2
[0061] The electrode substrate was the same as in Comparative Example 1 (i.e., without any chemical bonding modification), but the compacted electrode surface was coated with the same soluble functional coating as in Example 1 to evaluate the consequences of relying solely on channels without skeletal bonding. Cell B2 was fabricated.
[0062] Comparative Example 3
[0063] The substrate was prepared in the same manner as in Example 1, possessing a complete chemical covalent bond network. However, the parameters of the soluble coating on the electrode surface were set as follows: W = 400 μm, H = 2 μm, D = 200 μm.
[0064] Substitute into the formula to calculate: This is far below the formula's lower limit of 1.5. It is used to manufacture battery cell B3.
[0065] Comparative Example 4
[0066] Ordinary LFP powder (unmodified with hydrogen peroxide / ammonia, without surface hydroxyl groups) was used. The remaining processes were the same as in Example 1, including aluminum foil corona treatment, PAA-CMC crosslinking adhesive system, and vacuum high-temperature drying, and the same soluble functional coating was applied to the electrode surface. Cell B4 was thus produced.
[0067] Comparative Example 5
[0068] The substrate preparation was the same as in Example 1. The parameters of the soluble coating were adjusted to: W=1200μm, H=8μm, D=100μm.
[0069] Substitute into the formula to calculate: It exceeds the upper limit of 5.5. It is then used to make battery cell B5.
[0070] The following tests were performed on the electrode sheets and fully charged cells of the above embodiments and comparative examples: 1. Dry electrode 180° peel strength (N / m): Tests the peel force between the active material layer of the unfilled dry electrode and the current collector aluminum foil.
[0071] 2. Electrolyte wetting rate (%): After vacuum injection, the electrode was allowed to stand for 6 hours, and then disassembled to observe the proportion of dark-colored wetting area.
[0072] 3. Long-term cycling capacity retention (%): The capacity retention was recorded after 1500 continuous cycles at 1C / 1C ratio under 25°C conditions.
[0073] The test results are shown in Table 1.
[0074] Table 1
[0075]
[0076] The analysis of the above test results is as follows: 1. Superiority of the fully covalently bonded network: Comparative Example 1, based on the physical bonding of PVDF and smooth aluminum foil, has a peel strength of only 48 N / m. In contrast, the peel strength of the dry electrode in Example 1 jumps significantly to 135 N / m, achieving a mechanical property improvement of over 2.5 times. This is mainly due to the synergistic effect of the PAA-CMC crosslinking network, aluminum foil-ester bond anchoring, and LFP-ester bond anchoring, which endow the electrode with extremely strong mechanical toughness, fundamentally ensuring structural stability.
[0077] 2. Synergistic effect of soluble coating and bonding network: Compared with Comparative Example 2, although the coating opened up channels and increased the wettability to 97.2%, the underlying electrode still had weak physical bonding (43 N / m). After the channels dissolved, the matrix compaction was destroyed, resulting in severe delamination during long cycles. The capacity retention rate dropped sharply to 79.6% after 1500 cycles. Example 1, on the other hand, maintained a wettability of 96.5% while locking the electrode through a covalent bond network, achieving a cycle capacity retention rate as high as 94.2%.
[0078] 3. The necessity of LFP hydroxylation modification: In Comparative Example 4, the LFP particles were not grafted with hydroxyl groups (the LFP particle surface lacked -OH). The binder network could only achieve polymer self-crosslinking and binder anchoring to aluminum foil, lacking the chemical anchoring link between the binder and the active particles. The particles and matrix degenerated into physical encapsulation. Therefore, its peel strength dropped to 92 N / m, and the cycle capacity retention dropped to 87.5%. This proves that the "covalent bridge" must completely cover the active particle interface to achieve high stability.
[0079] 4. Guiding significance of coating parameter relationship: Embodiments 1 and 2 of the present invention strictly control the parameter range within the range of 1.5 to 5.5, effectively balancing high injection efficiency and strong mechanical support.
[0080] Below the lower limit (Comparative Example 3, calculated value 0.28): Due to the small cross-sectional area of the coating microchannels, the capillary force after dissolution is insufficient to overcome the fluid resistance of the high-pressure compacted LFP, and the wetting rate is only 81.5%, failing to exert the flow guiding effect.
[0081] When the value exceeds the upper limit (Comparative Example 5, calculated value 6.78): the electrode wettability is extremely high (99.5%), but the excessive coating occupies too much of the electrode's physical space, leaving excessively large voids after dissolution, severely damaging the solid-solid support framework. The electrode peel strength drops to 85 N / m, the active layer structure collapses rapidly during cyclic charging and discharging, and the cycle capacity retention drops to 83.2%.
[0082] 5. Advantages of gradient design: Example 3 introduces a thickness gradient distribution, which greatly improves the dry core problem in the central area, with a wetting rate of up to 99.1% and a retention rate of up to 95.5% after 1500 cycles.
[0083] In summary, the present invention breaks through the bottleneck of mutual constraints between energy density, wetting efficiency and long cycle life of lithium iron phosphate cathode sheets by systematically reconstructing from microscopic molecular-level chemical esterification to macroscopic gradient microchannel conduction, and has broad market application prospects.
[0084] It should be noted that the contents not described in detail in this specification are existing technologies known to those skilled in the art, and will not be elaborated here.
[0085] Based on the disclosure and teachings of the foregoing specification, those skilled in the art can make changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments described above, and any obvious improvements, substitutions, or modifications made by those skilled in the art based on the present invention are within the scope of protection of the present invention. Furthermore, although some specific terms are used in this specification, these terms are only for convenience of explanation and do not constitute any limitation on the present invention.
Claims
1. A highly stable lithium iron phosphate battery cathode, characterized in that, include: The modified aluminum foil treated with corona discharge has a micro-rough structure on its surface and is grafted with hydroxyl functional groups. A positive electrode active material layer is coated on at least one surface of the modified aluminum foil, the positive electrode active material layer comprising lithium iron phosphate positive electrode active material, a conductive agent and a crosslinking composite binder; the surface of the lithium iron phosphate positive electrode active material is hydroxylated and grafted with surface hydroxyl groups; A soluble functional coating is formed by intermittently coating the surface of the positive electrode active material layer and curing it. The soluble functional coating extends through the width direction of the positive electrode sheet and is used to dissolve and form a flow channel when the electrolyte is injected. The crosslinked composite adhesive is a composite adhesive with a three-dimensional network structure formed by in-situ crosslinking of polyacrylic acid and carboxymethyl cellulose through an esterification condensation reaction. The free carboxyl groups in the crosslinked composite adhesive that do not participate in the esterification condensation reaction undergo in-situ dehydration condensation reactions with the hydroxyl functional groups on the surface of the modified aluminum foil and the hydroxyl groups on the surface of the lithium iron phosphate positive electrode active material, respectively, to form a covalent bonded network.
2. The high-stability lithium iron phosphate battery positive electrode sheet according to claim 1, characterized in that, The characteristic parameters of the soluble functional coating satisfy the following relationship: Where: W is the width of a single functional coating, in μm; H is the thickness of a single functional coating, in μm; T is the thickness of the positive electrode active material layer after roll forming, in μm; D is the spacing between two adjacent functional coatings, in μm; d 50 The median particle size of the lithium iron phosphate cathode active material is expressed in μm.
3. The high-stability lithium iron phosphate battery positive electrode sheet according to claim 1, characterized in that, The soluble functional coating comprises the following components by weight percentage: 40% to 60% of the rapid solvent is selected from at least one of fluoroethylene carbonate and ethylene carbonate; 30% to 50% of the polymer gel backbone is selected from at least one of polyethylene oxide and polyvinylpyrrolidone; 5% to 15% of inorganic nanopropellers, selected from at least one of nano-silica and nano-alumina, with a particle size of 15 to 50 nm.
4. The high-stability lithium iron phosphate battery positive electrode sheet according to claim 1, characterized in that, In the positive electrode active material layer, the mass ratio of polyacrylic acid and carboxymethyl cellulose is (4~6):(1~1.5) to ensure that the polyacrylic acid has an excess of free carboxyl groups after esterification reaction with the carboxymethyl cellulose.
5. The high-stability lithium iron phosphate battery positive electrode sheet according to claim 1, characterized in that, The conductive agent is a composite conductive agent of one-dimensional carbon nanotubes and zero-dimensional conductive carbon black, with a mass ratio of (1~3):(2~4).
6. The high-stability lithium iron phosphate battery positive electrode sheet according to claim 1, characterized in that, Along the width direction of the positive electrode sheet, the thickness H of the soluble functional coating exhibits a distribution characteristic of gradually decreasing from the central region of the positive electrode sheet to the two side edge regions.
7. The high-stability lithium iron phosphate battery positive electrode sheet according to claim 1, characterized in that, The water contact angle of the modified aluminum foil surface is controlled between 10° and 30°, and the surface roughness Ra is 0.3 to 0.8 μm.
8. The high-stability lithium iron phosphate battery positive electrode sheet according to claim 1, characterized in that, In a unit mass of the lithium iron phosphate cathode active material, the molar content of hydroxyl groups grafted on its surface is 20~60 μmol / g, and it retains a complete olivine-type crystal structure.
9. A method for preparing a high-stability lithium iron phosphate battery positive electrode sheet as described in any one of claims 1-8, characterized in that, Includes the following steps: S1. Place the original lithium iron phosphate powder in a mixed aqueous solution containing hydrogen peroxide and dilute ammonia, and perform gentle hydrothermal stirring at 50℃~70℃ for 1~3h. After filtration, washing and drying, hydroxylated lithium iron phosphate positive electrode active material with hydroxyl groups grafted on the surface is obtained. S2. The positive electrode current collector aluminum foil is subjected to corona discharge treatment to obtain a modified aluminum foil with a micro-rough surface structure and grafted hydroxyl functional groups. S3. The hydroxylated lithium iron phosphate positive electrode active material, conductive agent, polyacrylic acid and carboxymethyl cellulose are mixed evenly to form an aqueous positive electrode slurry, which is uniformly coated on at least one surface of the modified aluminum foil. After staged drying and rolling, a substrate positive electrode sheet is obtained. In the high temperature vacuum stage of staged drying, polyacrylic acid and carboxymethyl cellulose undergo esterification condensation reaction to form a crosslinked composite binder, and the free carboxyl groups undergo in-situ condensation reaction with the hydroxyl groups on the surface of the modified aluminum foil and the hydroxyl groups on the surface of the hydroxylated lithium iron phosphate positive electrode active material. S4. On the surface of the positive active material layer of the substrate positive electrode sheet, the soluble functional coating is coated at intervals and vacuum cured at room temperature to form the lithium iron phosphate battery positive electrode sheet.
10. The method for preparing a high-stability lithium iron phosphate battery cathode according to claim 9, characterized in that, In step S3, the staged drying process includes: a normal pressure initial drying and dehydration stage with a temperature of 75℃~95℃ and a time of 0.5~1.5h; and a vacuum high-temperature crosslinking stage with a vacuum degree ≤-0.095MPa, a temperature of 140℃~160℃, and a holding time of 3~6h.